The State of Economic Development in Nepal - Adhikari, Bimal (International Journal of Social Sciences and Management, 2018)
This paper highlights the importance of measuring poverty through a multitude of approaches. This paper also discusses the current economic condition of Nepal using indices that emphasize financial aspects as well as by using indices that go beyond commercial elements. The overarching goal of this paper is to provide a comprehensive understanding of the state of poverty and economic development in Nepal. Based on the findings of this paper, the author finds access to cooking fuel, proper floor, sanitation, education facilities, and adequate nutrition to be the binding constraints on Nepal’s developmental aspirations. Targeted investment in these areas will certainly help to reduce widespread poverty. Int. J. Soc. Sc. Manage. Vol. 5, Issue-1: 43-45